STRATEGI GURU DALAM MENGEMBANGKAN PERHATIAN DAN KETERLIBATAN ANAK TUNAGRAHITA BERAT MELALUI METODE BERMAIN DAN BERNYANYI: STUDI KASUS SKHN 02 KOTA SERANG - Nurul Khoerunisa; Yahdinil Firda Nadirah (STKIP Subang, 2026)
This study aims to describe the teacher’s strategies in developing attention and engagement of a student with severe intellectual disability through play and singing methods at SKHN 02 Kota Serang. Students with severe intellectual disability have significantly below-average intellectual functioning as well as limitations in communication, social interaction, and adaptive behavior, thus requiring concrete and individualized learning approaches. This research employed a descriptive qualitative method, involving one first-grade student as the subject and the classroom teacher, who also serves as the guidance and counseling teacher, as the main informant. Data were collected through observations and semi-structured interviews, then analyzed through data reduction, data display, and conclusion drawing. The findings show that the consistent use of play and singing methods effectively improves the student’s attention and engagement during learning activities. Singing, body movements, simple games, and positive reinforcement were shown to help the student understand instructions, reduce impulsive behavior, and enhance imitation and social interaction skills. The success of these strategies is also influenced by the teacher’s ability to provide positive reinforcement, serve as a behavioral role model, and adjust learning activities to the student’s physical condition. This study emphasizes that concrete, multisensory, and empathetic learning approaches are highly effective for students with severe intellectual disability. Therefore, play and singing methods can serve as relevant and applicable strategies to enhance engagement and developmental progress in children with special needs.